Assessment of the knowledge of the subjects of the training process about psychological preparation in sports - Levina, I.L.; Artemiev, A.A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to assess the level of knowledge about the process and content of the psychological preparation of athletes among the subjects of the educational process, including athletes, coaches and parents of athletes. Methods and structure of the study. An online survey of 195 people was conducted, of which 98 athletes, 35 coaches, 62 parents of young athletes. To conduct the survey, questionnaires were used to identify knowledge about psychological preparation and its content. Results and conclusions. The survey revealed that the level of formation of ideas of coaches, athletes and parents of young athletes about the content of psychological preparation, ways to control the psychological state of an athlete in the process of training activities, preparation and participation in competitions, is low. Testing of the pre-start state has never been carried out in the majority of the athletes surveyed or was carried out using ineffective methods of suggestion and self-hypnosis, coach's settings and self-orders. In practice, coaches pay little attention to the issues of goal-setting, familiarization with the tasks and plan of the training cycle, pre-competitive preparation, the composition of the participants in the competition, seconding on the eve of the competition, analysis of the results of the competition. The results of the study actualize the development of a system of psychological preparation for all subjects of the training process, including coaches, athletes and their parents.